2019
DOI: 10.7752/jpes.2019.s5289
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This review wants to provide a summary of selected literature from the past 10 years on gender equity in P.E. It aims at providing an overview of the current research, while suggesting viable solutions to encourage girls to take a more active role in sport and physical activity. To ensure the respect of gender identity in education, the quality of teaching is crucial. Therefore, we argue that there is greater need for research in the field of gender equity in PE. While much research focused on how gender repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In line with this issue, Mayorga et al [ 36 ] suggested that unequal treatment is one of the barriers perceived by teenagers when doing physical activity, subsequently influencing their habits as adults. Moreover, Sánchez et al [ 37 ] stated that the role played by teachers and their behavior concerning gender is conditioned by the influence of other factors, such as socioeconomic, environmental, family, or cultural variables.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this issue, Mayorga et al [ 36 ] suggested that unequal treatment is one of the barriers perceived by teenagers when doing physical activity, subsequently influencing their habits as adults. Moreover, Sánchez et al [ 37 ] stated that the role played by teachers and their behavior concerning gender is conditioned by the influence of other factors, such as socioeconomic, environmental, family, or cultural variables.…”
Section: Introductionmentioning
confidence: 99%
“…In some example studies, many school subjects aimed to implement SD in their classes in terms of environmental resources in natural sciences [24] or promoting ecological habits in plastic and visual education [25]. On the other hand, as far as the social dimension is concerned, in some cases, didactic interventions are carried out in the area of citizenship and human rights, which is related to social and civic values and aims to make students aware of the gender inequalities that exist today and the struggle that women have been waging for years to eradicate these inequalities to understand the concepts of patriarchy, equality, and co-education and to put the latter two into practice [26]. On the other hand, didactic units (DDUU) implement active methodologies, placing the students at the center of their own learning, such as cooperative play, with the recreation of real situations in which to integrate attitudes of equality [27].…”
Section: Social Dimension Of Sustainable Development: Co-education At...mentioning
confidence: 99%